Behavior prediction of corrugated steel plate shear walls with openings. (November 2015) - Farzampour, Alireza; Laman, Jeffrey A.
Abstract: Corrugated steel plate and simple steel plate shear wall construction is a widely accepted and efficient lateral force resisting construction. The widespread use is motivated by the large initial stiffness, high level of energy absorption, and ability to accommodate openings. There is a dearth of information regarding the detailed nonlinear, inelastic behavior of corrugated steel plate shear walls, particularly walls with openings. Presented here are the results of a detailed, numerical parametric study comparing corrugated steel plate and simple steel plate shear walls, with and without openings. Parameters studied are plate thickness, angle of corrugation, opening size, and opening placement. Behaviors of interest for comparison are initial stiffness, ultimate strength, energy absorption, force–displacement relationship. The present study results indicate that the use of trapezoidal corrugated steel shear walls increases initial lateral stiffness, increases energy absorption and increases ductility while it reduces ultimate strength. In addition, the corrugated steel plate shear wall postpones the ultimate strength and degradation point relative to a corresponding unstiffened simple steel plate shear wall, which is a desirable characteristic for seismic resistance. An ultimate strength prediction procedure for corrugated steel plate shear walls with optimized rectangular opening position is developed and proposed. Highlights: Corrugated steel shear walls limit the plastic strains due to special geometry. Construction of openings off the diagonal is suggested for CSSW. CSSW shows higher initial stiffness and ductility compared to SSW. A proposed ultimate strength prediction for CSSW with an opening is provided. CSSW indicates higher energy absorption compared to SSW.